Online National Health Agency Mask Guidance for the Public in Light of COVID-19: Content Analysis - Laestadius, Linnea; Wang, Yang; Ben Taleb, Ziyad; Kalan, Mohammad Ebrahimi; Cho, Young; Manganello, Jennifer (JMIR Publications, 2020)
BackgroundThe rapid global spread of the coronavirus disease (COVID-19) has compelled national governments to issue guidance on the use of face masks for members of the general public. To date, no work has assessed how this guidance differs across governments. ObjectiveThis study seeks to contribute to a rational and consistent global response to infectious disease by determining how guidelines differ across nations and regions. MethodsA content analysis of health agency mask guidelines on agency websites was performed in late March 2020 among 25 countries and regions with large numbers of COVID-19 cases. Countries and regions were assigned across the coding team by language proficiency, with Google Translate used as needed. When available, both the original and English language version of guidance were reviewed. ResultsAll examined countries and regions had some form of guidance online, although detail and clarity differed. Although 9 countries and regions recommended surgical, medical, or unspecified masks in public and poorly ventilated places, 16 recommended against people wearing masks in public. There were 2 countries that explicitly recommended against fabric masks. In addition, 12 failed to outline the minimum basic World Health Organization guidance for masks. ConclusionsOnline guidelines for face mask use to prevent COVID-19 in the general public are currently inconsistent across nations and regions, and have been changing often. Efforts to create greater standardization and clarity should be explored in light of the status of COVID-19 as a global pandemic.